Socialization of e-Tracer Study for College Alumni - Rizaldi Akbar; Imilda; Sarboini; Junaidi (AJAD : Jurnal Pengabdian kepada Masyarakat, 2022)
This activity aims to provide alumni understanding regarding the importance of mapping graduates as one of the standards for measuring the quality of a university. Socialization activities are carried out using the method of implementing service activities consisting of 3 stages, namely; 1) Observation, 2) Seminar and Training, and 3) Evaluation and Reflection. Socialization activities have an impact on alumni understanding regarding graduate mapping, which is very important to do as one of the standards for measuring the quality of a university. The participants involved did not meet the team's expectations, 100 people were planned but only 43 people participated, this became a reference in increasing understanding efforts for graduates before what every university management must do before students complete higher education.